„Ces pitoyables truffes d’Italie“: Die französisch-italienische Rivalität auf dem europäischen Trüffelmarkt seit 1700. Zu einer Geschichte des Gastrochauvinismus und des Terroir - Rittersma, Rengenier C. (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
This article seeks to investigate the hitherto unexplored phenome- non of gastrochauvinism, by focussing on the French-Italian rivalry in truffle affairs since 1700. Its starting point is that seemingly trivial phenomena such as gastronomy and gastronomic products are pivotal, as far as the French and Italian self-perception is concerned. It tries to demonstrate this by unravelling the historical dynamics which urged Italian and French authors to claim the superiority of the Piedmontese white truffle respectively of the Périgord or the Umbrian black truffle. By doing this, it also contributes in a preliminary way to a history of the concept of terroir.